Age- and gender-specific incidence of new asthma diagnosis from childhood to late adulthood. (July 2019) - Honkamäki, Jasmin; Hisinger-Mölkänen, Hanna; Ilmarinen, Pinja; Piirilä, Päivi; Tuomisto, Leena E.; Andersén, Heidi; Huhtala, Heini; Sovijärvi, Anssi; Backman, Helena; Lundbäck, Bo; Rönmark, Eva; Lehtimäki, Lauri; et al.
Abstract: Background: Asthma is currently divided into different phenotypes, with age at onset as a relevant differentiating factor. In addition, asthma with onset in adulthood seems to have a poorer prognosis, but studies investigating age-specific incidence of asthma with a wide age span are scarce. Objective: To evaluate incidence of asthma diagnosis at different ages and differences between child- and adult-diagnosed asthma in a large population-based study, with gender-specific analyzes included. Methods: In 2016, a respiratory questionnaire was sent to 8000 randomly selected subjects aged 20–69 years in western Finland. After two reminders, 4173 (52.3%) subjects responded. Incidence rate of asthma was retrospectively estimated based on the reported age of asthma onset. Adult-diagnosed asthma was defined as a physician-diagnosis of asthma made at ≥ 18 years of age. Results: Among those with physician-diagnosed asthma, altogether, 63.7% of subjects, 58.4% of men and 67.8% of women, reported adult-diagnosed asthma. Incidence of asthma diagnosis was calculated in 10-year age groups and it peaked in young boys (0–9 years) and middle-aged women (40–49 years) and the average incidence rate during the examined period between 1946 and 2015 was 2.2/1000/year. Adult-diagnosed asthma became the dominant phenotype among those with physician-diagnosed asthma by age of 50 years and 38 years in men and women, respectively. Conclusions: Asthma is mainly diagnosed during adulthood and the incidence of asthma diagnosis peaks in middle-aged women. Asthma diagnosed in adulthood should be considered more in clinical practice and management guidelines. Highlights: Incidence of new asthma diagnosis is the highest in young boys and middle-aged women. The adult-diagnosed asthma phenotype is common however insufficiently studied. Adult-diagnosed asthma in an over 50-year-old is more probable than child-diagnosed.